The Impact of Fiscal Deficit on Economic Growth: Evidence from Europe (International Journal of Applied Research in Management and Economics, 2021)
The purpose of this paper is to determine the impact of fiscal deficit on economic growth to find out whether it is possible to promote economic growth through reduction of the gap between government revenue and expenditures. The sample for empirical analysis consists of thirty-seven European countries according to United Nations approach. We used panel regression to test stated hypothesis. The findings demonstrate that in the case of developed countries the fiscal deficit reduction could be one of the tools of accelerating economic growth. For developing countries, this method should not be used, as the deficit has no significant impact on GDP per capita.